(untitled) (Olhar de Professor, 2020)
The article discusses the National Literacy Assessment (ANA) in the context of educational literacy policies and large-scale assessments in Brazil. The objective is to analyze the repercussions of ANA in political-pedagogical actions adopted by Curitiba Municipal Secretariat of Education (SME) to overcome the insufficient levels of reading and writing in its network of schools. This is a quantitative and qualitative research that analyzes INEP results on ANA and the content of the interviews conducted with SME coordinators and pedagogues. It is concluded that the maintainer recognizes as the main policy to elevate to literacy learning the continuing education based on the Curricular Guidelines for the Municipal Schools of Curitiba, justifying that the contents coincide with those measured by ANA. It is verifiedthat continuing education does not emphasize the assessment of learning linked to diagnostic data of ANA and the political-pedagogical demands of the school context.